Electron spin resonance studies on deuterated nitroxyl spin probes used in Overhauser‐enhanced magnetic resonance imaging. (1st February 2017) - David Jebaraj, D.; Utsumi, Hideo; Milton Franklin Benial, A.
Abstract : The electron spin resonance studies were carried out for 2 mm concentration of 14 N‐labeled and 15 N‐labeled 3‐carbamoyl‐2, 2, 5, 5‐tetramethyl‐pyrrolidine‐1‐oxyl, 3‐carboxy‐2, 2, 5, 5‐tetramethyl‐pyrrolidine‐1‐oxyl, 3‐methoxycarbonyl‐2, 2, 5, 5‐tetramethyl‐pyrrolidine‐1‐oxyl and their deuterated nitroxyl radicals using X‐band electron spin resonance spectrometer. The electron spin resonance line shape analysis was carried out. The electron spin resonance parameters such as linewidth, Lorentzian component, signal intensity ratio, rotational correlation time, hyperfine coupling constant and g ‐factor were estimated. The deuterated nitroxyl radicals have narrow linewidth and an increase in Lorentzian component, compared with undeuterated nitroxyl radicals. The dynamic nuclear polarization factor was observed for all nitroxyl radicals. Upon 2 H labeling, about 70% and 40% increase in dynamic nuclear polarization factor were observed for 14 N‐labeled and 15 N‐labeled nitroxyl radicals, respectively. The signal intensity ratio and g ‐value indicate the isotropic nature of the nitroxyl radicals in pure water. Therefore, the deuterated nitroxyl radicals are suitable spin probes for in vivo / in vitro electron spin resonance and Overhauser‐enhanced magnetic resonance imaging modalities. Copyright © 2017 John Wiley & Sons, Ltd. Abstract : The figure shows electron spin resonance experimental and simulated spectra of  mm 14 N labeled (a) undeuterated 3‐carbamoyl‐2, 2, 5, 5‐tetramethyl‐pyrrolidine‐1‐oxyl and (b) deuterated carbamoyl‐2, 2, 5, 5‐tetramethyl‐pyrrolidine‐1‐oxyl.